Motivation and work incentives in standards of human resource management in the public sector - Castro Pérez, Luis Alonso (2018)
Given the finding of lack of motivation programs and work incentives in public sector workers, the study aims to determine how the regulations on human potential management takes into account such factors we consider first order for effectiveness in the performance of public functions. The research covers two periods: the first comprises since 1884 to 2008 and the second from 2008 to 2015, the latter referred to the creation of the National Civil Service Authority (SERVIR).